Ultrahigh-strength concrete and preparation method thereof
By introducing load-bearing steel fibers, aramid fibers, and reinforcing microparticles into ultra-high strength concrete, and combining the dispersion and bonding effects of hydroxypropyl methylcellulose ether and polyvinyl alcohol-1799, the problem of insufficient seismic performance of ultra-high strength concrete is solved, achieving high strength and good seismic performance.
Patent Information
- Application Number
- CN202511048959.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-11-07
AI Technical Summary
Existing ultra-high strength concrete is insufficient in terms of seismic performance, making it difficult to meet the seismic requirements of super high-rise buildings and long-span bridges.
By employing a combination of carrier steel fibers, carrier aramid fibers, and reinforcing microparticles, shrinkage cracks are suppressed during the concrete hydration process. The high strength of steel fibers and the toughness of aramid fibers, combined with the filling effect of reinforcing microparticles, improve the density of the concrete structure. Furthermore, the dispersion and bonding effects of hydroxypropyl methylcellulose ether and polyvinyl alcohol-1799 enhance the seismic performance of the concrete.
It improves the strength and seismic resistance of concrete, reduces crack formation, enhances the density and durability of the structure, and extends its service life.
Smart Images

Figure BDA0005522568330000081 
Figure BDA0005522568330000091
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of concrete processing, and more particularly, it relates to a super high-strength concrete and a preparation method thereof. BACKGROUND
[0002] The super high-strength concrete is a cement-based composite material with super high mechanical properties achieved by fine material proportioning and process, and is widely used in fields of super high-rise building columns and beams, large-span bridges, building curtain walls, and decorative components.
[0003] The super high-strength concrete has high compressive strength, can significantly improve the structural bearing capacity, has good water resistance and corrosion resistance, has certain freeze-thaw resistance and chemical corrosion resistance, and has a long service life in marine environment; however, the building and bridge components prepared from the super high-strength concrete have poor seismic performance.
[0004] Therefore, how to prepare a new concrete with high strength and good seismic effect is a problem to be solved. SUMMARY
[0005] In order to prepare a new concrete with high strength and good seismic effect, the present application provides a super high-strength concrete and a preparation method thereof.
[0006] In a first aspect, the present application provides a super high-strength concrete, which adopts the following technical scheme: The super high-strength concrete comprises the following raw materials by weight: cement 320-340 parts, fly ash 40-60 parts, mineral powder 90-110 parts, water 155-165 parts, sand 640-660 parts, crushed stone 1000-1100 parts, additive 7.4-7.9 parts, carrier steel fiber 10-16 parts, carrier aramid fiber 5-10 parts, and reinforcing particles 10-20 parts.
[0007] By adopting the above technical scheme, the carrier steel fiber, the carrier aramid fiber, and the reinforcing particles are matched, in the hydration process of the concrete, the aramid fiber can inhibit shrinkage cracks and reduce the generation of micro-cracks, and the high strength of the steel fiber and the filling effect of the reinforcing particles are utilized to improve the density of the concrete structure, thereby improving the strength of the concrete; at the same time, the steel fiber bears tensile stress in the concrete, and the aramid fiber has good toughness, so that when the concrete is impacted, the stress can be dispersed to avoid the generation of cracks, so that the concrete for preparing large-volume bridges has super high strength and good seismic effect.
[0008] Preferably, the carrier steel fiber is a pretreated steel fiber obtained by polishing the surface of the steel fiber, then bonding a hydroxypropyl methyl cellulose ether solution, and then bonding a carrier molecular sieve; the mass ratio of the pretreated steel fiber to the hydroxypropyl methyl cellulose ether solution and the carrier molecular sieve is 1:0.12-0.2:0.1-0.18.
[0009] By adopting the above technical solution, the surface roughness of the steel fiber is increased after polishing treatment, which facilitates stable bonding of the hydroxypropyl methyl cellulose ether solution, and then the carrier molecular sieve can be stably adhered to the surface of the steel fiber in cooperation with the good bonding effect of the hydroxypropyl methyl cellulose ether solution.
[0010] The carrier molecular sieve fills the micro-pores of the concrete, improves the structural density, cooperates with the delayed exothermic peak of the pore structure to reduce temperature stress cracks, and simultaneously utilizes the dispersion effect of the hydroxypropyl methyl cellulose ether to uniformly disperse the steel fiber, so that the steel fiber is not prone to produce holes or uneven strength problems during the vibration process of the ultra-high strength concrete. The hydroxypropyl methyl cellulose ether can also connect with the cementitious materials in the concrete, further improving the structural density and connection effect of the concrete, thereby improving the strength and anti-seismic effect of the concrete. The hydroxypropyl methyl cellulose ether can also improve the toughness and ductility of the concrete, further improving the anti-seismic effect of the concrete.
[0011] Preferably, the carrier molecular sieve is obtained by treating a molecular sieve with a polyvinyl alcohol-1799 solution.
[0012] By adopting the above technical solution, the pores and surface of the molecular sieve adhere polyvinyl alcohol-1799. During the vibration and hydration of the concrete, as the hydration temperature increases, the polyvinyl alcohol-1799 gradually swells slightly. Although the hydration heat of the concrete does not reach above 90℃, the hydration heat of the large-volume bridge concrete member can reach about 80℃. The polyvinyl alcohol-1799 easily swells slightly at a temperature of about 80℃. The slight swelling can fill the shrinkage gaps of the concrete, thereby improving the structural density of the concrete, so that the ultra-high strength concrete has high strength and good anti-seismic effect.
[0013] The polyvinyl alcohol-1799 remaining in the molecular sieve can also swell slightly to fill the pores of the molecular sieve, avoiding excessive water absorption of the molecular sieve, which affects the strength of the concrete and the water resistance and corrosion resistance of the concrete during use, thereby prolonging the service life of the ultra-high strength concrete.
[0014] The hydroxyl in the hydroxypropyl methyl cellulose ether, the hydroxyl of the surface polyvinyl alcohol-1799 microparticle of the carrier molecular sieve can be connected by hydrogen bond attraction, and the cementing material can also be connected with the hydroxyl, further improving the connecting effect of the carrier steel fiber and the cementing material, cooperating with the hydrophobicity of the methoxy, reducing the water loss amount of the mass concrete in the high temperature hydration process, reducing the generation of cracks, and improving the strength.
[0015] Preferably, the steel fiber is a wave-shaped steel fiber, and the abrasive is a diamond particle, and the polishing is performed for 3-5 min.
[0016] By adopting the above technical scheme, the wave-shaped steel fiber is combined with the polishing treatment, the specific surface area of the steel fiber is improved, an efficient anchoring effect can be formed, the tensile stress can be effectively transmitted, the fiber can bear the bending moment by spanning the cracks, the glass curved surface can enhance the stress dispersion particles, and the fracture can be delayed, the uniformly dispersed and randomly distributed wave-shaped steel fibers can form a three-dimensional network, the oblique crack propagation can be prevented, the impact energy can be further absorbed, the strength of the concrete can be improved, and the anti-seismic performance can be improved.
[0017] Preferably, the carrier aramid fiber is prepared from aramid fiber, ethyl cellulose complex liquid and silicon dioxide microparticles in a mass ratio of 1:0.1-0.3:0.1-0.2.
[0018] By adopting the above technical scheme, the bonding effect of the ethyl cellulose complex liquid is utilized, the silicon dioxide microparticles are easily adhered to the surface of the aramid fiber, the silicon hydroxyl in the silicon dioxide microparticles is easily connected with the hydroxyl on the surface of the carrier steel fiber, the bonding effect of the carrier aramid fiber and the cementing material of the concrete can be improved, the structural density of the concrete can be improved, and thus the strength of the concrete can be improved.
[0019] When the concrete is impacted, the connecting effect of the silicon dioxide microparticles is utilized first to ensure the stability of the carrier aramid fiber in the structure of the concrete, the flexible over-buffering effect of the ethyl cellulose is combined to buffer the stress concentration, the aramid fiber is prevented from being debonded from the cementing material, gravel and other substances, finally the excellent toughness and impact resistance of the aramid fiber are combined to bear the impact force, prevent the generation of cracks, inhibit the penetration of the cracks, and have good explosion-proof performance, thereby improving the anti-seismic effect of the concrete.
[0020] Preferably, the ethyl cellulose complex liquid is prepared from an ethyl cellulose solution and a cetyl stearyl alcohol solution in a mass ratio of 1:0.2-0.4.
[0021] By adopting the technical scheme, the ethyl cellulose solution and the cetyl stearyl alcohol solution are both dissolved in ethanol, the cetyl stearyl alcohol has a certain lubricating and dispersing effect, can promote the uniform dispersion of the load aramid fiber in the concrete, and in cooperation with the ethyl cellulose and the aramid fiber, a uniform distribution of the rigid-flexible buffer layer is formed, the strength and the impact resistance of the concrete are improved, so that the concrete has the advantages of high strength and good anti-seismic effect.
[0022] The melting point of the cetyl stearyl alcohol is about 48-50℃, which can reach the melting point in the hydration process of the concrete, the hot melt migration of the cetyl stearyl alcohol further fills the pores around the load aramid fiber, and the structure compactness of the concrete is further improved, so that the strength and the anti-seismic effect of the concrete are improved.
[0023] Preferably, the reinforcing microparticles are composed of heavy calcium carbonate, aluminum silicate and hydrophobic silica gel microparticles with a mass ratio of 1:0.5-0.8:0.2-0.5.
[0024] By adopting the technical scheme, the heavy calcium carbonate can fill the small pores of the concrete, the compactness and the strength of the concrete are enhanced, the layered structure of the aluminum silicate further forms a connection network in the concrete, so as to resist the impact force and prevent the generation and expansion of cracks, and the hydrophobic silica gel microparticles have good elasticity and toughness, which can not only buffer the impact force, but also fill the voids and restore the shape, so as to ensure the anti-seismic effect of the concrete.
[0025] Preferably, the hydrophobic silica gel microparticles are prepared by treating silica gel microparticles with silane coupling agent KH-570.
[0026] By adopting the technical scheme, the silica gel microparticles have good waterproof effect, the building bridge is immersed in water for a long time, the structure has high compactness, and in cooperation with the waterproof property, the durability of the concrete building bridge is improved, and the service life is prolonged.
[0027] Preferably, the admixture is composed of a water reducing agent and an air entraining agent with a mass ratio of 1:0.1-0.15.
[0028] By adopting the technical scheme, the water reducing agent and the air entraining agent cooperate to reduce the cracks of the concrete and reduce the pores of the concrete, so as to further improve the strength and the anti-seismic effect of the concrete.
[0029] In a second aspect, the application provides a preparation method of super high strength concrete, which adopts the following technical scheme: A preparation method of super high strength concrete, comprising the following steps: S1, uniformly mixing and stirring cement, fly ash, mineral powder, sand and gravel to obtain initial mixture; S2, the carrier steel fiber, the carrier aramid fiber and the reinforced microparticle in the initial mixture are mixed and stirred uniformly, then water and the additive are added and continue to be stirred uniformly to obtain a mixture; S3, the mixture is poured and cured to obtain the concrete.
[0030] By adopting the above technical scheme, the prepared concrete has high strength, good anti-seismic effect, good water resistance and corrosion resistance, and long service life.
[0031] In summary, the present application has the following advantages: 1, the carrier steel fiber, the carrier aramid fiber and the reinforced microparticle cooperate, in the hydration process of the concrete, the aramid fiber can inhibit the shrinkage crack and reduce the generation of microcracks, and the high strength of the steel fiber and the filling effect of the reinforced particle are used to improve the density of the concrete structure, thereby improving the strength of the concrete; at the same time, the steel fiber bears tensile stress in the concrete, and the aramid fiber has good toughness, which can disperse stress and avoid crack when the concrete is impacted, so that the concrete for preparing large-volume bridges has ultrahigh strength and good anti-seismic effect.
[0032] 2, the dispersion effect of the hydroxypropyl methyl cellulose ether is used to uniformly disperse the steel fiber, so that the steel fiber is not prone to have holes or uneven strength problems during the vibration of the ultrahigh strength concrete, the hydroxypropyl methyl cellulose ether can also connect with the cementitious material in the concrete, further improving the structural density and connection effect of the concrete, thereby improving the strength and anti-seismic effect of the concrete, the hydroxypropyl methyl cellulose ether can also improve the toughness and ductility of the concrete, further improving the anti-seismic effect of the concrete. DETAILED DESCRIPTION
[0033] The present application is further described in detail below in combination with examples.
[0034] Preparation example of carrier steel fiber The hydroxypropyl methyl cellulose ether in the following raw materials is purchased from Beijing Wantu Ming Technology Co., Ltd.; and the other raw materials are ordinary commercially available.
[0035] Preparation example 1: the carrier steel fiber is prepared by the following method: The molecular sieve is immersed and dispersed in a polyvinyl alcohol-1799 solution, ultrasonically dispersed at 20 kHz for 5 min, then the molecular sieve is filtered out and dried to obtain a carrier molecular sieve; the average particle size of the molecular sieve is 120 μm, the mass fraction of the polyvinyl alcohol-1799 solution is 0.5%, and the solvent is water at 95℃; Put 10 kg steel fiber in high speed mixer for stirring, abrasive is diamond particle, polishing time is 4 min, steel fiber is wave shape steel fiber, average length is 3 mm, obtain pretreated steel fiber, on the surface of 1 kg pretreated steel fiber, evenly spray 0.15 kg hydroxypropyl methyl cellulose ether solution, mass fraction of hydroxypropyl methyl cellulose ether solution is 1%, solvent is water, then add 0.15 kg carrier molecular sieve, the adding speed of carrier molecular sieve is 100 g / min, in the adding process, pretreated steel fiber is continuously stirred under the rotation speed of 120 r / min, after mixing uniformly, dry, disperse to pretreated steel fiber mutual non-stick aggregation, obtain carrier steel fiber.
[0036] Preparation example 2: the difference between this preparation example and preparation example 1 is that: Put molecular sieve in polyvinyl alcohol-1799 solution for soaking and dispersing, ultrasonic dispersion under the condition of 20 kHz for 5 min, then filter out molecular sieve, dry, obtain carrier molecular sieve; average particle size of molecular sieve is 120 μm, mass fraction of polyvinyl alcohol-1799 solution is 0.5%, solvent is water of 95 ℃; Put 10 kg steel fiber in high speed mixer for stirring, abrasive is diamond particle, polishing time is 3 min, steel fiber is wave shape steel fiber, average length is 3 mm, obtain pretreated steel fiber, on the surface of 1 kg pretreated steel fiber, evenly spray 0.2 kg hydroxypropyl methyl cellulose ether solution, mass fraction of hydroxypropyl methyl cellulose ether solution is 1%, solvent is water, then add 0.1 kg carrier molecular sieve, the adding speed of carrier molecular sieve is 100 g / min, in the adding process, pretreated steel fiber is continuously stirred under the rotation speed of 120 r / min, after mixing uniformly, dry, disperse to pretreated steel fiber mutual non-stick aggregation, obtain carrier steel fiber.
[0037] Preparation example 3: the difference between this preparation example and preparation example 1 is that: Put molecular sieve in polyvinyl alcohol-1799 solution for soaking and dispersing, ultrasonic dispersion under the condition of 20 kHz for 5 min, then filter out molecular sieve, dry, obtain carrier molecular sieve; average particle size of molecular sieve is 120 μm, mass fraction of polyvinyl alcohol-1799 solution is 0.5%, solvent is water of 95 ℃; Put 10 kg steel fiber in a high-speed blender for stirring, the abrasive is diamond particles, the polishing time is 5 min, the steel fiber is a wave-shaped steel fiber, the average length is 3 mm, to obtain the pretreated steel fiber, 0.12 kg of hydroxypropyl methyl cellulose ether solution is uniformly sprayed on the surface of 1 kg of the pretreated steel fiber, the mass fraction of the hydroxypropyl methyl cellulose ether solution is 1%, the solvent is water, then 0.18 kg of the carrier molecular sieve is added, the adding speed of the carrier molecular sieve is 100 g / min, the pretreated steel fiber is continuously stirred at a speed of 120 r / min during the adding process, after mixing uniformly, drying and dispersing to the pretreated steel fiber, the pretreated steel fiber does not agglomerate, to obtain the carrier steel fiber.
[0038] Preparation example of the carrier aramid fiber The following raw materials are all ordinary commercial products.
[0039] Preparation example 4: the carrier aramid fiber is prepared by the following method: Put the ethyl cellulose in ethanol and stir until completely dissolved to obtain a 1% mass fraction of ethyl cellulose solution, the ethoxy content of the ethyl cellulose is 48%; put the cetyl stearyl alcohol in ethanol and stir until completely dissolved to obtain a 2% mass fraction of cetyl stearyl alcohol solution, mix 1 kg of the ethyl cellulose solution and 0.3 kg of the cetyl stearyl alcohol solution and stir uniformly to obtain an ethyl cellulose composite solution; the mass fraction of ethanol is 95%; Spray 0.2 kg of the ethyl cellulose composite solution on the surface of 1 kg of the aramid fiber, then add 0.15 kg of the silica microparticles, the average length of the aramid fiber is 2 mm, the average particle size of the silica microparticles is 5 μm, the adding speed of the silica microparticles is 100 g / min, the aramid fiber is continuously stirred at a speed of 120 r / min during the adding process, after mixing uniformly, drying and dispersing to the aramid fiber, the aramid fiber does not agglomerate, to obtain the carrier aramid fiber.
[0040] Preparation example 5: the difference between this preparation example and preparation example 4 is: Put the ethyl cellulose in ethanol and stir until completely dissolved to obtain a 1% mass fraction of ethyl cellulose solution, put the cetyl stearyl alcohol in ethanol and stir until completely dissolved to obtain a 2% mass fraction of cetyl stearyl alcohol solution, mix 1 kg of the ethyl cellulose solution and 0.2 kg of the cetyl stearyl alcohol solution and stir uniformly to obtain an ethyl cellulose composite solution; 0.1kg ethyl cellulose composite liquid is uniformly sprayed on the surface of 1kg aramid fiber, then 0.1kg silica microparticles are added, the average length of the aramid fiber is 2mm, the average particle size of the silica microparticles is 5μm, the adding speed of the silica microparticles is 100g / min, the aramid fiber is continuously stirred at a speed of 120r / min during the adding process, after mixing uniformly, the aramid fiber is dried and dispersed to be not agglomerated, and the carrier aramid fiber is obtained.
[0041] Preparation Example 6: The difference between the present preparation example and Preparation Example 4 is that: The ethyl cellulose is stirred in ethanol until completely dissolved to obtain a 1% mass fraction ethyl cellulose solution, the cetyl stearyl alcohol is stirred in ethanol until completely dissolved to obtain a 2% mass fraction cetyl stearyl alcohol solution, 1kg of the ethyl cellulose solution and 0.4kg of the cetyl stearyl alcohol solution are mixed and stirred uniformly to obtain the ethyl cellulose composite liquid; 0.3kg ethyl cellulose composite liquid is uniformly sprayed on the surface of 1kg aramid fiber, then 0.2kg silica microparticles are added, the average length of the aramid fiber is 2mm, the average particle size of the silica microparticles is 5μm, the adding speed of the silica microparticles is 100g / min, the aramid fiber is continuously stirred at a speed of 120r / min during the adding process, after mixing uniformly, the aramid fiber is dried and dispersed to be not agglomerated, and the carrier aramid fiber is obtained.
[0042] Preparation Example of hydrophobic silica microparticles The following raw materials are all ordinary commercial products.
[0043] Preparation Example 7: The hydrophobic silica microparticles are prepared by the following method: The silica microparticles with an average particle size of 10μm are dispersed in silane coupling agent KH-570 under an ultrasonic frequency of 20kHz for 10min, then the silica microparticles are filtered out, dried and dispersed to be not agglomerated, and the hydrophobic silica microparticles are obtained. Example
[0044] The polycarboxylic acid superplasticizer in the following raw materials is purchased from Hubei Benben Technology Co., Ltd., model BBJ-10; other raw materials are all ordinary commercial products.
[0045] Example 1: A super high strength concrete: Cement 330 kg, fly ash 50 kg, slag 100 kg, water 160 kg, sand 652 kg, gravel 1050 kg, admixture 7.68 kg, carrier steel fiber 14 kg, carrier aramid fiber 8 kg, reinforcing microparticle 15 kg; the carrier steel fiber is the carrier steel fiber prepared in Preparation Example 1, the carrier aramid fiber is the carrier aramid fiber prepared in Preparation Example 4, the reinforcing microparticle is composed of heavy calcium carbonate, aluminum silicate and hydrophobic silica gel microparticle with a mass ratio of 1:0.6:0.4, and the hydrophobic silica gel microparticle is the hydrophobic silica gel microparticle prepared in Preparation Example 7; the admixture is composed of polycarboxylic acid high-efficiency water reducing agent and air entraining agent with a mass ratio of 1:0.12, and the air entraining agent is triterpene saponin; the cement is P.O. 42.5 ordinary portland cement; the particle size of the gravel is 5-25 mm continuous gradation; the medium sand is II region medium sand with a clay content <1.0%; the fly ash is F class II grade fly ash with a water content <0.2%; the slag is S95 grade slag powder with an activity index (7d) of 82% and a water content of 0.2%; The preparation method is as follows: S1, uniformly mix and stir the cement, fly ash, slag, sand and gravel to obtain a preliminary mixture; S2, uniformly mix and stir the carrier steel fiber, carrier aramid fiber and reinforcing microparticle in the preliminary mixture, then continue to uniformly stir the water and admixture to obtain a mixture; S3, the mixture is poured and cured to obtain the concrete.
[0046] Example 2: The difference between this example and Example 1 is that: Cement 320 kg, fly ash 40 kg, slag 90 kg, water 155 kg, sand 640 kg, gravel 1000 kg, admixture 7.4 kg, carrier steel fiber 10 kg, carrier aramid fiber 5 kg, reinforcing microparticle 10 kg; the carrier steel fiber is the carrier steel fiber prepared in Preparation Example 2, the carrier aramid fiber is the carrier aramid fiber prepared in Preparation Example 5, the reinforcing microparticle is composed of heavy calcium carbonate, aluminum silicate and hydrophobic silica gel microparticle with a mass ratio of 1:0.8:0.2, and the hydrophobic silica gel microparticle is the hydrophobic silica gel microparticle prepared in Preparation Example 7; the admixture is composed of polycarboxylic acid high-efficiency water reducing agent and air entraining agent with a mass ratio of 1:0.1.
[0047] Example 3: The difference between this example and Example 1 is that: Cement 340 kg, fly ash 60 kg, slag 110 kg, water 165 kg, sand 660 kg, gravel 1100 kg, additive 7.9 kg, carrier steel fiber 16 kg, carrier aramid fiber 10 kg, reinforcing microparticle 20 kg; the carrier steel fiber is the carrier steel fiber prepared in Preparation Example 3, the carrier aramid fiber is the carrier aramid fiber prepared in Preparation Example 6, the reinforcing microparticle is composed of heavy calcium carbonate, aluminum silicate and hydrophobic silica gel microparticle with a mass ratio of 1:0.5:0.5, and the hydrophobic silica gel microparticle is the hydrophobic silica gel microparticle prepared in Preparation Example 7; the additive is composed of polycarboxylic acid high-efficiency water reducing agent and air entraining agent with a mass ratio of 1:0.15.
[0048] Example 4: The difference between this example and Example 1 is that: The carrier steel fiber is prepared by replacing the carrier molecular sieve with the same mass of molecular sieve in the preparation process.
[0049] Example 5: The difference between this example and Example 1 is that: The carrier steel fiber is prepared by replacing the hydroxypropyl methyl cellulose ether solution with the same mass of carboxymethyl cellulose solution in the preparation process.
[0050] Example 6: The difference between this example and Example 1 is that: The carrier aramid fiber is prepared by replacing the ethyl cellulose complex solution with the same mass of ethyl cellulose solution in the preparation process.
[0051] Example 7: The difference between this example and Example 1 is that: The reinforcing microparticle is prepared by replacing the hydrophobic silica gel microparticle with the same mass of silica gel microparticle in the preparation process.
[0052] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: The carrier steel fiber is replaced with steel fiber with the same mass in the raw materials.
[0053] Comparative Example 2: The difference between this comparative example and Example 1 is that: The carrier aramid fiber is replaced with aramid fiber with the same mass in the raw materials.
[0054] Comparative Example 3: The difference between this comparative example and Example 1 is that: The carrier aramid fiber is replaced with polypropylene fiber with the same mass in the raw materials.
[0055] Performance detection test 1. Mechanical strength detection Concrete is prepared by using the methods of Examples 1-7 and Comparative Examples 1-3 respectively, and the size of the large volume test block is 1m 3 × 1m × 1m . The 28d compressive strength is detected according to GB / T50081, and the data is recorded.
[0056] 2. Anti-seismic performance detection The concrete was prepared by the method of Example 1-7 and Comparative Example 1-3 respectively, a 6-level earthquake was simulated by a simulated earthquake platform, and a 1m 3 The bridge building model was vibrated under the condition of 6-level earthquake for 2 min, after 10 min of interval, it was vibrated again under the condition of 6-level earthquake for 2 min, after 10 min of interval, the operation was repeated for 6 times, then the compressive strength of the concrete was detected, the data was recorded, and the cracking area of the concrete surface per square meter was recorded, and the data was recorded.
[0057] 3. Anti-seismic performance detection The concrete was prepared by the method of Example 1-7 and Comparative Example 1-3 respectively, the anti-permeation pressure of the standard test block was detected according to the detection standard GB / T50082, and the size of the standard test block was 150mmx150mmx150mm.
[0058] Table 1 Performance test table It can be seen from Examples 1-3 and Table 1 that the concrete prepared in the application has high strength and good anti-seismic effect, and good water permeation resistance, which can meet the requirements of building bridge concrete, and the concrete has good durability and long service life.
[0059] It can be seen from Examples 1 and Examples 4-7 and Table 1 that in the preparation process of the steel fiber of Example 4, the same quality of molecular sieve is used to replace the carrier molecular sieve, compared with Example 1, the strength of the concrete prepared in Example 4 is lower than that of Example 1, the post-earthquake strength loss is greater than that of Example 1, the cracking area is greater than that of Example 1, and the anti-permeation pressure is lower than that of Example 1, which shows that after the molecular sieve is loaded with polyvinyl alcohol-1799, the structure density of the concrete can be improved, and the internal pores of the concrete can be filled during the shrinkage process, so that the mass concrete has high strength and good anti-seismic effect, prevents water permeation, prolongs the service life, and meets the requirements of bridge use.
[0060] In the preparation process of the steel fiber in Example 5, the carboxymethyl cellulose solution is used to replace the hydroxypropyl methyl cellulose ether solution with the same mass. Compared with Example 1, the strength of the concrete prepared in Example 5 is lower than that of Example 1, the post-earthquake strength loss is greater than that of Example 1, the cracking area is greater than that of Example 1, and the impermeable pressure is lower than that of Example 1. It is shown that although the carboxymethyl cellulose has viscosity and ensures early strength, the long-term strength is unstable, and the high-temperature condition of mass concrete makes the concrete performance worse. The hydroxypropyl methyl cellulose ether has good high-temperature stability, good late strength and durability, and can prolong the service life and durability of the concrete.
[0061] In the preparation process of the steel fiber in Example 5, the carboxymethyl cellulose solution is used to replace the hydroxypropyl methyl cellulose ether solution with the same mass. Compared with Example 1, the strength of the concrete prepared in Example 5 is lower than that of Example 1, the post-earthquake strength loss is greater than that of Example 1, the cracking area is greater than that of Example 1, and the impermeable pressure is lower than that of Example 1. It is shown that although the carboxymethyl cellulose has viscosity and ensures early strength, the long-term strength is unstable, and the high-temperature condition of mass concrete makes the concrete performance worse. The hydroxypropyl methyl cellulose ether has good high-temperature stability, good late strength and durability, and can prolong the service life and durability of the concrete. In the preparation process of the steel fiber in Example 5, the carboxymethyl cellulose solution is used to replace the hydroxypropyl methyl cellulose ether solution with the same mass. Compared with Example 1, the strength of the concrete prepared in Example 5 is lower than that of Example 1, the post-earthquake strength loss is greater than that of Example 1, the cracking area is greater than that of Example 1, and the impermeable pressure is lower than that of Example 1. It is shown that although the carboxymethyl cellulose has viscosity and ensures early strength, the long-term strength is unstable, and the high-temperature condition of mass concrete makes the concrete performance worse. The hydroxypropyl methyl cellulose ether has good high-temperature stability, good late strength and durability, and can prolong the service life and durability of the concrete.
[0062] In combination of Example 1 and Comparative Examples 1-3 and Table 1, it can be seen that the steel fiber is used to replace the steel fiber in the raw materials of Comparative Example 1 with the same mass. Compared with Example 1, the strength of the concrete prepared in Comparative Example 1 is lower than that of Example 1, the post-earthquake strength loss is greater than that of Example 1, the cracking area is greater than that of Example 1, and the impermeable pressure is lower than that of Example 1. It is shown that the polished steel fiber, in combination with the hydroxypropyl methyl cellulose ether solution and the carrier molecular sieve, can improve the bonding effect of the carrier steel fiber and the cementitious materials and other substances, improve the compactness of the concrete structure, prevent the generation of cracks, and improve the strength, anti-seismic effect and durability of the concrete.
[0063] In the raw materials of Comparative Example 2, the carrier aramid fibers are replaced with aramid fibers of the same mass. Compared with Example 1, the concrete prepared in Comparative Example 2 has lower strength, greater loss of post-shock strength, greater cracking area, and lower impermeability pressure than Example 1. This shows that the aramid fibers treated with the ethyl cellulose complex solution and the silicon dioxide microparticles can improve the bonding stability and structural density of the carrier aramid fibers in the concrete, thereby improving the strength and durability of the concrete.
[0064] In the raw materials of Comparative Example 3, the carrier aramid fibers are replaced with polypropylene fibers of the same mass. Compared with Example 1, the concrete prepared in Comparative Example 3 has lower strength, greater loss of post-shock strength, greater cracking area, and lower impermeability pressure than Example 1. This shows that although the polypropylene fibers can improve the strength of the concrete, they have poor effect on impact resistance, thereby affecting the anti-seismic effect. The polypropylene fibers and the cementitious materials only rely on the adhesion of the cementitious materials, which can easily affect the internal structural density and waterproof density of the concrete, thereby affecting the strength, water resistance, and anti-seismic effect of the concrete.
[0065] The specific embodiments are merely illustrative of the present application, and are not intended to limit the present application. Those skilled in the art can make modifications to the embodiments without creative contribution after reading the present specification, and the modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An ultra-high strength concrete, characterized by, The raw materials include cement 320-340 parts, fly ash 40-60 parts, mineral powder 90-110 parts, water 155-165 parts, sand 640-660 parts, gravel 1000-1100 parts, additive 7.4-7.9 parts, carrier steel fiber 10-16 parts, carrier aramid fiber 5-10 parts, and reinforcing microparticles 10-20 parts.
2. The ultra-high strength concrete according to claim 1, characterized in that: The carrier steel fiber is obtained by polishing the surface of the steel fiber, then bonding a hydroxypropyl methyl cellulose ether solution, and then bonding carrier molecular sieves. The mass ratio of the pretreated steel fiber to the hydroxypropyl methyl cellulose ether solution and the carrier molecular sieves is 1:0.12-0.2:0.1-0.
18.
3. The ultra-high strength concrete according to claim 2, wherein The carrier molecular sieves are obtained by treating molecular sieves with a polyvinyl alcohol-1799 solution.
4. The ultra-high strength concrete of claim 2, wherein The steel fiber is a wave-shaped steel fiber, and the abrasive is diamond particles, which are polished for 3-5 minutes.
5. The ultra-high strength concrete of claim 1, wherein The carrier aramid fiber is obtained by mixing aramid fiber, ethyl cellulose complex solution, and silica microparticles at a mass ratio of 1:0.1-0.3:0.1-0.
2.
6. The ultra-high strength concrete according to claim 5, wherein The ethyl cellulose complex solution is obtained by mixing an ethyl cellulose solution and a cetyl stearyl alcohol solution at a mass ratio of 1:0.2-0.
4.
7. The ultra-high strength concrete of claim 1, wherein The reinforcing microparticles are composed of heavy calcium carbonate, aluminum silicate, and hydrophobic silica gel microparticles at a mass ratio of 1:0.5-0.8:0.2-0.
5.
8. The ultra-high strength concrete according to claim 7, wherein The hydrophobic silica gel microparticles are obtained by treating silica gel microparticles with silane coupling agent KH-570.
9. The ultra-high strength concrete of claim 1, wherein The additive is composed of a water reducing agent and an air entraining agent at a mass ratio of 1:0.1-0.
15.
10. A method of producing a ultra high strength concrete according to any one of claims 1 to 9, characterized in that, The method comprises the following steps: S1, uniformly mixing cement, fly ash, mineral powder, sand, and gravel to obtain initial mixture; S2, adding carrier steel fiber, carrier aramid fiber, and reinforcing microparticles to the initial mixture, and then adding water and additive to obtain mixture; S3, pouring and curing the mixture to obtain concrete.